Problematika Pernikahan Usia Muda: Studi Kasus di Desa Mattirowalie, Kecamatan Libureng, Kabupaten Bone - Akhirudin - (Universitas Khairun, 2015)
According to the rule of marriage number 1, 1974 chapter 7 section 1 whichset the limitation of te age for men and women who will get marriage, theyhave been 19 years old for a man and 16 years old for woman. The objectiveof the study was to know the frequency of early marriage happen. The kind ofthe study was descriptive qualitative and the informant of determination wasconducted by purposive sampling, the data analyze of technique usingobservation, interview and documentation. Then it was analyzed by reduction,presentation and verification data. The result of the study showed earlymarriage happened by some factors, they are: the first, volition himself orherself (love each other), the second, the family factor (the parents look fortheir son’s or girl’s couple) the third, the tradition factor (to make their familyor relative to be close in that society), the fourth, economy factor (to reducethe parents’ outcome), the fifth, educational factor (their parents have lackknowledge for their son or daughter).